Electronic signatures and ethics - Srivastava, Aashish; Thomson, Stanley Bruce (My University, 2007)
The advent of the Internet once again raised the question as to what constitutes a signature and what form of signature should be used to sign electronic documents. This led legal jurists and academics to examine what a signature is. Traditionally, a signature is “the name of a person written with his or her own hand” (Merriam- Webster Online Dictionary, 2006), and since 439 AD in the Roman Empire, a signature authenticated wills (Nicholas, 1965). However, courts have accepted various other forms of signature such as initials, marks, rubber stamp, typed name, and a printed name.1 Thus the validity of a signature is not to be tested by its form but rather by the functions it performs (Reed, 2000).
Keywords: information security & privacy; IT security and ethics; security and forensic science and technology